An Analytical Study of Reading Difficulties among Secondary School Students in Sudan and Saudi Arabia (Architecture Image Studies, 2025)
This study explores the nature and causes of reading difficulties among secondary school students in Sudan and Saudi Arabia. Drawing on both quantitative and qualitative data, the study identifies key barriers such as limited reading fluency, insufficient background knowledge, and inadequate instructional practices. The findings call for targeted pedagogical interventions, improved teacher training, and curriculum enhancement to support reading development in English as a Foreign Language (EFL) contexts.